2016
DOI: 10.7567/apex.10.013002
|View full text |Cite
|
Sign up to set email alerts
|

Narrowing of antiferromagnetic domain wall in corundum-type Cr2O3 by lattice strain

Abstract: The effect of lattice strain on single-ion magnetic anisotropy and antiferromagnetic domain wall width in corundum-type Cr2O3 is studied using first-principles calculations and micromagnetics simulations. Without lattice strain, the domain wall width L DW is about 80 nm. When the lattice constant a is increased by 1–2%, L DW is reduced to less than 20 nm due to the increase in the single-ion anisotropy constant K 1 to on the order of 106 erg/cm3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Designing these two intermediate state is required with respect to each applications. In fact, the magnetic domain of Cr2O3 received increasing attentions toward device applications; Experimental demonstration of a local writing of exchange biased domain of Cr2O3/FM heterostructure, 23 theoretical study on domain wall dynamics, 24 and domain wall width 25 were reported recently. However, thus far, there's no attempt to control these two state actively.…”
mentioning
confidence: 99%
“…Designing these two intermediate state is required with respect to each applications. In fact, the magnetic domain of Cr2O3 received increasing attentions toward device applications; Experimental demonstration of a local writing of exchange biased domain of Cr2O3/FM heterostructure, 23 theoretical study on domain wall dynamics, 24 and domain wall width 25 were reported recently. However, thus far, there's no attempt to control these two state actively.…”
mentioning
confidence: 99%
“…Within the long wave-length approximation, it becomes γ 2 k = 1 − (ak) 2 /d for | k |= k and thereby assuming a spin anisotropy 67,68 at low temperature, the dispersion becomes parabolic in terms of k and reduces to the form ω k = Dk 2 + ∆ with D = JSa 2 / √ κ 2 + 2κ which is used in the main text. Note that the dispersion becomes linear in terms of k, ω k ∝ k, when there is no spin anisotropy K = 0, i.e., κ = 0.…”
Section: Discussionmentioning
confidence: 99%
“…where J > 0 parametrizes the antiferromagnetic exchange interaction between the nearest-neighbor spins and K > 0 is the easy-axis anisotropy 67,68 that ensures the magnetic Néel order along the z direction. Since the Hamiltonian is invariant under global spin rotations about the z axis, the z component of the total spin is a good quantum number (i.e.…”
Section: Topologically Trivial Afmentioning
confidence: 99%
See 2 more Smart Citations